PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN PT PIGEON INDONESIA - Mukhammad Adieb (Journal Of Communication Education, 2016)
ABSTRACT Various studies indicate job satisfaction and organizational commitment are the main factors that influence the willingness of employees to move. Employees who are dissatisfied with their jobs will lose commitment to the organization that would later withdraw in the form began to have thoughts to go out, find another job and wants to quit his job. The desire to move (turnover intention) is to watch by the company. Because of this impact turnover intention will be the actual turnover.This study aimed to examine the effect of variable job satisfaction and organizational commitment variables to variable turnover intention. The method used is descriptive and using stratified random sampling to determine the number of samples. From the analysis of the data found that job satisfaction is positively and significantly related to turnover intention, commitment organisation positive and significant effect on turnover intention.             When Job satisfaction and organization commitmen be examined together, the result is shows that Job Satisfaction have big influenced to turnover intention than and Organizationalcommitmen. Keywords: Job Satisfaction, Organizational Commitment, Turnover Intention